Remembering the German Democratic Republic divided memory in a united Germany - Clarke, David 1972-; Wölfel, Ute (Palgrave Macmillan, 2011)
Memories of and attitudes to the German Democratic Republic (GDR), or East Germany, within contemporary Germany are characterized by their variety and complexity, whilst the debate over how to remember the GDR tells us a lot about how Germans see themselves and their future. This volume provides a range of international perspectives. DAVID BATHRICK Professor of German and Jewish Studies, Cornell University, USA ANDREW BEATTIE Lecturer in German and European Studies, the University of New South Wales, Sydney, Australia ANDREW BICKFORD Associate Professor of Anthropology, George Mason University, Virginia, USA DAVID CLARKE Senior Lecturer in German, the University of Bath, UK MARY FULBROOK Professor of German History, University College London, UK COURTNEY GLORE CRIMMINS Department of Modern Languages and Literatures, Montclair State University, New Jersey, USA CLAIRE HYLAND Doctoral Student, the University of Bath, UK SARA JONES Leverhulme Early Career Fellow, the University of Bristol, UK BARBARA KÖNCZÖL DAAD-Fachlektorin for Contemporary German History, University of Cambridge, UK CHRISTIANE LAHUSEN Doctoral Student, Zentrum für Zeithistorische Forschung Potsdam, Germany RENÉ LEHMANN Research Fellow, Institute of Sociology, Friedrich-Alexander-University of Erlangen-Nuremberg, Germany ANDREAS LUDWIG Director, the Dokumentationszentrum Alltagskultur der DDR in Eisenhüttenstadt, Germany JOSIE MCLELLAN Senior Lecturer in Modern European History, the University of Bristol, UK RICHARD MILLINGTON Ph.D. Graduate, the University of Liverpool, UK ANNE-MARIE PAILHÈS Associate Professor of German, Université Paris Ouest Nanterre La Défense, France HELMUT PEITSCH Professor of German at the University of Potsdam, Germany JOANNE SAYNER Lecturer in Cultural Theory, Department of German Studies, University of Birmingham, UK UTE WÖLFEL Lecturer in German, the University of Reading, UK JENNY WÜSTENBERG Ph.D. Graduate in Political Science, the University of Maryland, College Park, USA STEFAN ZAHLMANN Professor for the History and Theory of Media Cultures, the University of Vienna, Austria